2020
DOI: 10.1371/journal.ppat.1008869
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage maturation from blood monocytes is altered in people with HIV, and is linked to serum lipid profiles and activation indices: A model for studying atherogenic mechanisms

Abstract: People with HIV (PWH) are at increased risk for atherosclerotic cardiovascular disease (ASCVD). Proportions of vascular homing monocytes are enriched in PWH; however, little is known regarding monocyte-derived macrophages (MDMs) that may drive atherosclerosis in this population. We isolated PBMCs from people with and without HIV, and cultured these cells for 5 days in medium containing autologous serum to generate MDMs. Differential gene expression (DGE) analysis of MDMs from PWH identified broad alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 98 publications
(136 reference statements)
5
12
0
Order By: Relevance
“…The observed intrinsic proinflammatory phenotype of monocytes in PLHIV was stable over time and associated with upregulation of proinflammatory pathways, most notably the IL-1β pathway. This corroborates a recent study showing a pronounced proinflammatory phenotype, including upregulation of IL1B , of monocyte-derived macrophages in PLHIV ( 38 ). Long-term epigenetic reprogramming of monocytes in response to microbes has been termed trained immunity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observed intrinsic proinflammatory phenotype of monocytes in PLHIV was stable over time and associated with upregulation of proinflammatory pathways, most notably the IL-1β pathway. This corroborates a recent study showing a pronounced proinflammatory phenotype, including upregulation of IL1B , of monocyte-derived macrophages in PLHIV ( 38 ). Long-term epigenetic reprogramming of monocytes in response to microbes has been termed trained immunity.…”
Section: Discussionsupporting
confidence: 93%
“…These data corroborate findings from earlier, smaller studies in PLHIV, which reported an increased production of pro-inflammatory cytokines to stimulation with ligands of TLR4 (30,31) or TLR7 (32,33) (38). Long-term epigenetic reprogramming of monocytes in response to microbes has been termed 'trained immunity'.…”
Section: Discussionsupporting
confidence: 89%
“…Methylation of selected SREBP1 CpG is also associated with adiposity (Justice et al, 2020). Also, SREBP1 has been implicated in establishing a proatherogenic lipid profile in monocytes (Bowman et al, 2020). In summary, several of the indicated genes have wellcharacterized functions in adipocytes, but evidence for regulation of blood cell homeostasis supports our differential methylation data.…”
Section: Discussionsupporting
confidence: 69%
“…It is extremely difficult to determine selective killing of very low numbers of HIV-infected macrophages in the patients and even in in vitro HIV-infected macrophages. The high variability in SM-mediated killing of ex vivo generated MDMs from monocytes of ART-treated and naïve untreated groups may also be due to the myeloid population in the patients which is exposed to a variety of inflammatory/anti-inflammatory cytokines and exposure to a variety of opportunistic infections 56 . Exposure to ARV drugs may be somewhat toxic to these cells and affect their ability to respond to stress by altering their mitochondrial function 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%